Analisis Peningkatan Kinerja Bisnis Jasa Persewaan Toga (Studi pada ToGraduation Semarang) - Nugroho, Ismail Dwi; Idris, Idris (Diponegoro Journal of Management, 2023)
ABSTRACT As one of the providers, ToGraduation intends to optimize these opportunities by analyzing weaknesses in all aspects of the business and exploiting the opportunities available. This research aims to find out whether the analysis of the development of the ToGraduation business can yield profits in the future. This research uses a qualitative methods with a descriptive approach. Data collection was carried out using documentation techniques obtained from ToGraduation financial statements and observations obtained from ToGraduation business activities. The total funding required is Rp678.006.106, divided into Rp.362.135.295 for investment costs and Rp. 315.870.813 for working capital costs in the first year of the project. After sensitivity calculations, the results showed Net Present Value (NPV) of Rp1.090.006.861, Internal Rate of Return (IRR) of 76%, Payback Period (PBP) of 1.8 years, and profitability index of 1.163. These results show that ToGraduation's rental business has a worthy future to operate.